Karakteristik Penderita Kusta Multi Basiller (MB) dengan Reaksi Erythema Nodosum Leprosum (ENL) di Poliklinik Kulit dan Kelamin RSUP Sanglah selama Tahun 2016-2018 - Putu Ayu Saraswati; Luh Made Mas Rusyati; IGAA Dwi Karmila (DiscoverSys Inc., 2019)
Introduction: Leprosy is still a burden on endemic countries such as Indonesia. As well as leprosy reaction is a problem associated with the cessation of treatment from leprosy patients. The purpose of this study was to do a description of the characteristics of leprosy patients with ENL reactions in the Skin and Sex Polyclinic of Sanglah Hospital Denpasar.Method: This study used a descriptive design with a retrospective approach conducted at the Skin and Sex Polyclinic of Sanglah General Hospital. A search related to the characteristics of leprosy patients who experienced an ENL reaction, then the data was presented in descriptive form.Results: Female gender tend to have more severe leprosy reactions (50%) compared to men. High income (50%), non-endemic area origin (44.8%), elementary school education level (44.4%), and active working (31.0%) tended to experience more severe leprosy reactions. And in this study more severe leprosy reactions were found in the multi-bacillary leprosy group (65.7%), whereas mild leprosy reactions were higher in the pauci-bacillary leprosy group (34.2%).Conclusion: The high rate of severe leprosy reaction requires special attention from both the government and health practitioners, so that there is an integrated management of leprosy, so that the population in Indonesia becomes healthier.